(untitled) (Research, Society and Development, 2022)
In Brazil, Dengue is one of the main public health problems due to its high degree of morbidity. Thus, the present work has as main objective to identify the behavior in the number of dengue cases in the State of Paraíba between the period from 2014 to 2017. To achieve the objectives, the research is an observational, descriptive and cross-sectional study. The area of this study was the state of Paraíba. Secondary data produced by the dengue surveillance system of all reported cases of the disease were used. The results showed that the year 2015 had the highest number of reported cases. The age group with the highest number of cases was from 20 to 39 years, and the most attended race was brown and the most reported sex was female. Finally, efforts are needed in campaigns that seek clarification and prevention of dengue to the population, in order to create a preventive culture from the change in people’s attitude, with regard to measures that favor the proliferation of the vector, highlighting, in in particular, women, as a target audience susceptible to illness and complications.